Bertrand Russell’s Philosophy and the Problem of Object: Logical Analysis versus Linguistic Analysis. - Damouche, Ouahiba (Dirasat: Human and Social Sciences, 2025)
Objectives: This study discusses the content, the form, and the independence of the external objects. It also examines the object’s relationship to other linguistic and scientific issues. Perceiving the object is what the words means. While what words refer to is the logical object, material objects are what constitute a fact. The role of the concepts of subject, object, logical form, universals, particulars, and relations in the solution of the problem of scientific knowledge are identified for the purpose of justifying the scientific knowledge. Methods: A linguistic logical analysis method is used to examine sentence structure and word meaning, order and their role in concepts construction. Syntax is used to understand the linguistic and logical constructions by reducing them to symbols and logical forms and reconstruction process starting from empirical meaning to formal level exemplified in a proposition . Results: Our findings show that the difficulty of distinguishing the form of the object from its empirical content leads to call objects facts. for the same reason, the object, which becomes a sense datum, also turns out to be a sensible percept. Therefore, the logical form is favored since it is is presented as the basis of certainty. Conclusions: The study shows that the logical objects became fused with Russell’s objective in reconstructing mathematics by justifying its logical basis on one side, and renders the scientific philosophy to mathematical philosophy on the other side. Yet, metaphysics is used for justification, and every thing becomes an object; in the most general sense, it is an object-based metaphysics.